Effectiveness of Cervicogenic Myofascial Release Combined with TENS in Managing Tension-Type Headache: A Quasi-Experimental Study - Chaitanya Basavaraju; Madhavan Iyengar; Bhavana Gadhavi; Advita Neville Deepak (The Bioscan, 2026)
Introduction: Tension-Type Headache (TTH) is one of the most common types of headache, typically presenting as a dull, aching, band-like pain around the head and neck, often linked with myofascial dysfunction and psychological stress. Non-pharmacological interventions such as Cervicogenic Myofascial Release (CMR) and Transcutaneous Electrical Nerve Stimulation (TENS) have shown promising outcomes in symptom alleviation. Objective: To assess the efficacy of combining Cervicogenic Myofascial Release with TENS in reducing headache severity, frequency, and neck-related disability among individuals with TTH.